PENGEMBANGAN MOTIVASI KERJA PEGAWAI DI BADAN KETAHANAN PANGAN KABUPATEN KUTAI TIMUR - Sri Yanti; Aji Ratna Kusuma; Adam Idris (Jurnal Paradigma (JP), 2019)
The purpose of this study is to describe and analyze the development of Employee Work Motivation in the Food Security. This type of research conducted by the author, including qualitative descriptive. Source data extracted from key informants and informant. Analysis of the data used is Interactive models. The results showed that the development of work motivation of employees in the Food Security East Kutai Regency is done through the provision of incentives, giving apprecition, work placement employees as expertise, providing the opportunity take part in education and training, as well as providing working facilities it can motivate employees to implementation job good. From the set parameters, such factors rated most powerful incentive to spur the spirit of employees in their duties. While the appreciation factor and the factor of education and training is quite motivating employees to perform their duties. While the factors of employment and provision of working facilities are less encouraging employee motivation.Keywords: Development, Employee, Work Motivation